2023
DOI: 10.3389/fvets.2023.1099170
|View full text |Cite
|
Sign up to set email alerts
|

Use of qualitative behavioural assessment to investigate affective states of housed dairy cows under different environmental conditions

Abstract: In addition to the reduction of suboptimal welfare, there is now a need to provide farmed animals with positive opportunities to provide confidence that they have experienced a life worth living. Diversification of the environment through environmental enrichment strategies is one suggested avenue for providing animals with opportunities for positive experiences. The provision of more stimulating environmental conditions has been widely implemented in other animal production industries, based on evidenced welf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…This is in contrast with our expectations, given that environmental enrichment strategies usually have positive effects on animal welfare. This effect was previously investigated in cows using QBA ( 40 ), showing that animals provided with enrichments, such as novel objects or access to an outdoor area, were more content, relaxed and positively occupied, and less fearful and bored than animals without enrichments. In our case, brushes cannot be considered a novel object, as they were always present in the barns, and the access to an outdoor area was not a novelty either, because it was present all year round.…”
Section: Discussionmentioning
confidence: 92%
“…This is in contrast with our expectations, given that environmental enrichment strategies usually have positive effects on animal welfare. This effect was previously investigated in cows using QBA ( 40 ), showing that animals provided with enrichments, such as novel objects or access to an outdoor area, were more content, relaxed and positively occupied, and less fearful and bored than animals without enrichments. In our case, brushes cannot be considered a novel object, as they were always present in the barns, and the access to an outdoor area was not a novelty either, because it was present all year round.…”
Section: Discussionmentioning
confidence: 92%
“…As play is a distinctive behaviour 19 , it might be possible to reduce the sampling frequency as long as the frequency remains twice the highest frequency in the signal 21 . This would extend the battery life of sensors and enable collection of extensive long-term data on play behaviour, which could provide an automated alternative to the time-consuming visual assessment of play behaviour and welfare status (Qualitative Behavioural Assessment) 22 .…”
Section: Introductionmentioning
confidence: 99%
“…These scores are then typically refined into multiple component scores, representing groups of related terms, through means of Principle Component Analysis (PCA). QBA has been utilized in the welfare assessment of wide variety of species (e.g., cows 25 , pigs 26 , sheep 27 , horses 28 , donkeys 29 , goats 30 , chickens 24 , dogs 22 , polar bears 31 , elephants 32 , dolphins 33 , salmon 34 ), as it is often suggested that included terms (such as ‘Playful’ or ‘Relaxed’) can be representative of an animal’s emotional state 7 , 26 . However, like all measurement tools, the process of continued validation is critical 26 and research exploring the validity of QBA as a reliable indicator of valence and arousal appears to have been limited.…”
Section: Introductionmentioning
confidence: 99%